MATERIAL GROUND FOR OPENING A PRE-TRIAL INVESTIGATION: THEORY AND PRACTICE - Juozapavičius, Audrius (Teisė, 2017)
The subject of this article is to define the concept of material ground for opening (beginning) a pre-trial investigation, identify problems of legal regulation and practice, offer the solutions. Relying on constitutional jurisprudence, legal regulation and basic doctrine, the author criticises prevalent concept of a restrictive interpretation of material ground for opening a pre-trial investigation and the doctrine of so-called “verification” acts, as well as its practice. On the ground of scientific analysis, it is concluded, that the notion of “data of a criminal act” defined in Article 168 Para 1 of the CCP (Code of Criminal Process) means factual circumstances of a criminal act, hence necessary and sufficient material ground for opening a pre-trial investigation is a suspicion based on concrete factual circumstances of a criminal act that a criminal act has been committed (initial suspicion). While deciding to open pre-trial investigation, the law of evidence does not apply – all evidence are collected only after opening of a pre-trial investigation. Also it is concluded that while deciding to open a pre-trial investigation, the argument of ultima ratio is not applied and pre-trial investigation is commonly opened for difficult to interpret and apply criminal acts.